Fuel Properties and Combustion Kinetics of Hydrochar Prepared by Hydrothermal Carbonization of Corn Straw - Xianjun Xing; Fangyu Fan; Suwei Shi; Yongqiang Xing; Yongling Li; Xuefei Zhang; Jing Yang (BioResources, 2016)
The potential of using hydrothermal carbonization (HTC) on corn straw (CS) was studied for the production of solid fuel. The effects of hydrothermal conditioning on the mass yield, energy yield, higher heating value (HHV), H/C and O/C atomic ratios, the morphology, and equilibrium moisture content (EMC) of hydrochars were examined by varying the reaction temperature (170 °C, 200 °C, 230 °C, and 260 °C) and the residence time (15 min and 30 min). The results demonstrated that the solid fuel properties of hydrochar produced at 230 °C for 30 min had an appropriate HHV of 20.51 MJ/kg, a mass yield of 64.80%, and an energy yield of 77.41%. The physical structure changed because of hydrothermal carbonization and the hydrophobicity of hydrochar increased in comparison to raw corn straw after hydrothermal carbonization. The combustion characteristics and kinetic parameters of raw corn straw and hydrochar were calculated based on the thermogravimetric curves according to Arrhenius equation. The activation energies of hydrochars were larger than that of raw corn straw. The comprehensive combustibility index (S) of raw corn straw was greater than that of hydrochar when the reaction temperature and residence time were 230 °C and 30 min, respectively.